Polish political parties’ stand on the Silesian issue exemplified by their attitude towards the Silesian Autonomy Movement (Economic and Political Thought, 2015)
The article analyses the attitudes of the Polish political parties towardsthe ‘Silesian issue’ based on their attitude towards Ruch Autonomii Śląska(RAŚ) [the Silesian Autonomy Movement]. Using the available data analysisas well as the method of individual semi-structured in-depth interviews, thepaper provides up-to-date knowledge about the above-mentioned field. Thepredominant majority of Polish political parties (both at the central and theregional level) have a negative attitude towards RAŚ and its postulates –among others: the autonomy for the regions, recognition of the Silesians asa separate nation or the status of the Silesian language. The paper attemptsto systematise the Polish political parties’ position on the ‘Silesian issue’exemplified by their attitudes towards RAŚ.